Canonical variate residuals-based contribution map for slowly evolving faults. (April 2019) - Li, Xiaochuan; Yang, Xiaoyu; Yang, Yingjie; Bennett, Ian; Collop, Andy; Mba, David
Highlights: The development of a new monitoring index based on statistics T 2,   Q and T d . The development of a CVR-based contribution method for the monitoring of slowly evolving faults. Validated using data captured from a CSTR simulation program and an operational industrial centrifugal pump. Abstract: The superior performance of canonical variate analysis (CVA) for fault detection has been demonstrated by a number of researchers using simulated and real industrial data. However, applications of CVA to fault identification of industrial processes, especially for faults that evolve slowly, are not widely reported. In order to improve the performance of traditional CVA-based methods to slowly developing faults, a novel diagnostic approach is put forward to implement incipient fault diagnosis for dynamic process monitoring. Traditional CVA fault detection approach is extended to form a new monitoring index based on indices, Hotelling's T 2,   Q and a canonical variate residuals (CVR)-based monitoring index T d . As an alternative to the traditional CVA-based contributions, a CVR-based contribution plot method is proposed based on Q and T d statistics. The proposed method is shown to facilitate fault detection by increasing the sensitivity to incipient faults, and aid fault identification by enhancing the contributions from fault-related variables and suppressing the contributions from fault-free variables. The CVR-based method has been demonstrated to outperform traditional CVA-based diagnostic methods for fault detection and identification when validated on slowly evolving faults in a continuous stirred tank reactor (CSTR) system and an industrial centrifugal pump.